1,3-Dipolar Cycloaddition of 3-Amino Oxindole-Based Azomethine Ylides and O-Vinylphosphonylated Salicylaldehydes for Diastereoselective Synthesis of Oxindole Spiro-P,N-polycyclic Heterocycles - Huang, Tiao; Liu, Li; Wang, Qinghe; Wu, Mingshu; Kong, Dulin (Synthesis, 2020)
An efficient stereoselective assembly strategy for the construction of pyrrolidin-2,3′-oxindole cis-fused phosphadihydrocoumarins was established. The process involves the condensation of O-vinylphosphonylated salicylaldehydes and 3-amino oxindoles followed by intermolecular cycloaddition with high diastereoselectivity and atom economy.
Keywords: 3-amino oxindole; azomethine ylide; dipolar cycloaddition; pyrrolidin-2,3′-oxindoles; cis-fused phosphadihydrocoumarins; O-vinylphosphonylated salicylaldehyde